Effectiveness of Crash course on Emotional intelligence among Undergraduate Nursing students - Joshi, Binal; Joel Emmanue, Franny; Vageriya, Vipin (International Journal of Psychosocial Rehabilitation, 2024)
A pre-experimental study to examine the effectiveness of crash course on emotional intelligence was carried out among 30 undergraduate nursing students with predefined inclusion and exclusion criteria. A standardized tool SSEIT was used to assess the emotional intelligence. Self-structured crash course on emotional intelligence was delivered to the group for 7 days in two sessions. Descriptive and inferential statistics were used for data analysis. A significant difference between the pretest and post test scores of emotional intelligences (117.33 to 137.33, t= 08.02 is more than tabulated t value 2.021 at 0.05 level of significance with df=29. The study concluded that selfstructured crash course on emotional intelligence was effective in improving emotional intelligence among undergraduatenursing students.